Value-driven intellectual capital : how to convert intangible corporate assets into market value - Sullivan, Patrick H. (John Wiley & Sons New YorkUS, 2000)
Explores how organizations create and extract value through intellectual capital. Discusses how to determine the kind of value desired; how to organize the firm in order to obtain it; and, how to measure the value realized.